America's Philosopher: John Locke in American Intellectual Life by Claire Rydell Arcenas

(untitled) (Western Libraries at The University of Western Ontario, 2024)
Review of Claire Rydell Arcenas’s America’s Philosopher: John Locke in American Intellectual Life (Chicago and London: University of Chicago Press, 2023)